Structural changes of the photosynthetic apparatus under osmotic stress in different Triticum aestivum and Aegilops biuncialis genotypes - Gáspár, László (Acta Biologica Szegediensis, 2002)
The photosynthetic apparatus of three Aegilops biuncialis genotypes differing in the annual rainfall of their habitat (1050 mm, 550 mm and 225 mm), two drought resistant Triticum aestivum genotypes and one with high crossing efficiency (Mv9Kr1) were examined under the effect of osmotic stress brought about by PEG in the nutrient solution. Two Aegilops genotypes Ae.b.225 and Ae.b.550 proved to be relatively stable under osmotic stress showing only slight changes of Chi concentration of the leaves and relative amount of chlorophyll proteins (CPs) in the thylakoids. In spite of the structural stability, PEG treatment considerably lowered the yield of low temperature fluorescence emission. The relative increase of emission around 700 nm can be attributed to LHCII aggregation related quenching processes. More pronounced changes in the relative amount of CPs were observed in Triticum genotypes and in Ae.b. 1050. These changes, which included the relative decrease of PSII core complex and the relative increase of LHCII, reversed during the recovery period. Low temperature fluorescence yield decreased evenly throughout the spectrum and the lack of relative increase around 700 nm points to a quenching process other than LHCII aggregation. The Ae.b.1050 and Mv9Kr1 wheat genotypes proved to be the most susceptible to osmotic stress with more pronounced decrease of PSIICC and increase of LHCII, less fluorescence decline in the emission spectra, and slower recovery of these parameters.